Pengaruh Penggunaan Multimedia Interaktif Terhadap Kemampuan Pemahaman Pupujian Sunda di SMPN 2 Kramatmulya Kelas VII - Opah Ropiah; Ipan Ripai (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
Sundanese pupujian (praise) material is a part of Sundanese language subjects in junior high school grade VII. Sundanese praise is an oral literature that must be preserved. In Sundanese praise there are educational values that can be used as guidelines for behavior. This study aim to describe the effect of interactive multimedia-based learning media in understanding Sundanese praise by using experimental study. Experimental desain used in this study is pretest-posttest one sample group design. This research was done in grade VII students in the junior high school 2 Kramatmulya. The results showed that using interactive multimediasignificantly could increased student’s understanding of Sundanese praise. T-test was conducted on the pretest and posttest data of the study. From the test results it is known that the Sig. (2-tailed) value of 0.001. This means Sig (2-tailed) 0.05. It can be concluded that there are differences in the mean scores of students before and after learning by using Sundanese Pupujian learning media based on interactive multimedia.